Photodegradation of Permethrin using Photocatalyst Montmorillonite-TiO2 - Addy Rachmat; Muhammad Said; Fatma Fatma; Hardi Aji Badarwi; A.M. Ramadhan (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Photocatalyst Montmorillonite-TiO2 was synthesized using template CTAB and natural clay for degradation of Permethrin. The porosity and crystalline phase of catalyst were evaluated using N2 sorption analyzer and XRD diffraction. Permethrin photodegradation was optimized by varying reactant volume, irradiation time and initial concentration. Montmorillonite enhanced by CTAB showed typical porosity i.e. specific surface area, pore radii and pore volume for layer material. It properties decreased as this host material was impregnated with TiO2. XRD diagram indicated that space between layers of Montmorillonite expanded up to 4.7 Å. The diffractogram also confirmed that TiO2 formed an Anatase phase instead of Rutile. Photodegradation conducted at several condition showed relatively low photocatalytic activity. The highest photodegradation was achieved at 50 mL of Permethrin with initial concentration 10 ppm and 100 minutes’ irradiation. Keywords: Permethrin, Photodegradation, Montmorillonite-TiO2